The Role of Biology Teachers in Building Students’ Interest in Learning in Cross-Interest Biology Subject - A.S. Alonemarera (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
This study aims to determine the role of biology teachers in building student learning interest in cross-interest biology subjects in class X IPS at SMA Negeri 1 Toari. Descriptive type research with qualitative and quantitative approaches. Data collection techniques using interviews, questionnaires and observation. With total sampling technique, the sample in this study was determined to be 1 biology teacher and 16 students of class X social studies. The results showed the teacher as: (1) demonstrator 90.1%, very good category, including explaining the material using sentences that are easy to understand. (2) Motivator 80.55%, very good category, including the way the teacher always encourages students to dare to express opinions. (3) Class manager 91.32%, very good category, including ensuring the class is in a clean condition. (4) mediator and facilitator 60.93%, good category, by how the teacher uses varied learning media. (5) evaluator of 77.83%, good category, including by assessing and returning student assignments. Quantitatively, the average role of biology teachers is 80.15%. Thus, it is concluded that the role of biology teachers in building students' interest in learning in the cross-interest subject of biology class X IPS at SMA Negeri 1 Toari is categorized as very good.